2022
DOI: 10.1021/acs.jpcb.2c00101
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Parameterization of Ion–Surfactant Interactions in Dissipative Particle Dynamics Using Setschenow Coefficients

Abstract: Dissipative particle dynamics (DPD) simulations of nonionic surfactants with an added salt show that the Setschenow relationship is reproduced; that is, the critical micelle concentration is log-linearly dependent on the added salt concentration. The simulated Setschenow coefficients depend on the DPD bead–bead repulsion amplitudes, and matching to the experimentally determined values provides a systematic method to parameterize the interactions between salt ion beads and surfactant beads. The optimized ion-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 72 publications
(140 reference statements)
1
3
0
Order By: Relevance
“…Comparing the charge density and CCIS values in the presence of KCl and CaCl 2 , the higher affinity of the Ca 2+ to the negatively charged particle is clearly visible since these parameters decreased significantly as the counterion’s valence was increased. This finding can be explained by the fact that divalent cations are more effective in charge screening than monovalent ones, as reported earlier in other particle–electrolyte systems. ,, …”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…Comparing the charge density and CCIS values in the presence of KCl and CaCl 2 , the higher affinity of the Ca 2+ to the negatively charged particle is clearly visible since these parameters decreased significantly as the counterion’s valence was increased. This finding can be explained by the fact that divalent cations are more effective in charge screening than monovalent ones, as reported earlier in other particle–electrolyte systems. ,, …”
Section: Resultssupporting
confidence: 69%
“…This finding can be explained by the fact that divalent cations are more effective in charge screening than monovalent ones, as reported earlier in other particle–electrolyte systems. 11 , 18 , 53 56 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By using the relationship provided by Groot and Warren, the DPD interaction parameters, a ij , between beads were calculated by using the Flory–Huggins parameters reported in the diverse literature studies. However, we were unable to find data for PGMA, thus, we assumed that PLA and PGMA are identical in the model and represented these two molecules by the same interaction parameters. Notice that there have been recent attempts to parametrize DPD interactions to achieve a quantitative agreement with experimental data, and the results from these efforts are very encouraging; in here, however, we focus on a qualitative comparison with experimental phenomenology rather than a precise quantitative comparison. Table lists the Flory–Huggins parameters for all different molecules simulated in this work; as can be seen in the table, the Flory–Huggins parameter associated with the pair PEG-PLA is negative, indicating that these two polymers are compatible.…”
Section: Model and Methodsmentioning
confidence: 98%
“…Up until now, direct parameterisation of charged beads has been largely neglected, with most authors taking the simple approach to assign beads as having the same a ij interactions as water. However, an interesting study by Lavagnini et al 90 indicated that for salt solutions, even for nonionic surfactants, the calculated CMC values depend largely on the ion-tail repulsion parameter, meaning that this is likely to be a source of error in our approach.…”
Section: Comparison With Earlier Studiesmentioning
confidence: 98%